Exchange rate regime and wage determination in Central and Eastern Europe - Gunther Schnabl; Christina Ziegler (Center for Economic Studies and ifo Institute (CESifo), 2008)
After the eastern enlargement of the European Union due to increasing labor market integration, wage determination and monetary integration in Central and Eastern Europe have become key issues in European economic policy making. Based on the Scandinavian model of wage adjustment by Lindbeck (1979), we intend to analyze the role of exchange rates in the wage determination process of the Central and Eastern European countries to identify which exchange rate strategy contributes to faster wage convergence in Europe. Panel estimations reveal a robust negative relationship between exchange rates and wage growth. This suggests that workers in countries with fixed exchange rates are likely to benefit from higher wage increases.
Keywords: C23; J30; F31; O52; 330; Wage policy; labor markets; exchange rate regime; Central and Eastern Europe; Wechselkurssystem; Lohnbildung; Lohnniveau; Entwicklungskonvergenz; Entwicklungskonvergenz; EU-Staaten (Osteuropa)